Using Puzzle Games To Increase Student Involvement In Learning in Elementary School - Kamiliatus Zahroh; Misbahul Khoir; Rifatus Safira (Penerbit Hellow Pustaka, 2024)
This study aims to increase student involvement in learning, namely IPAS on the material of plant parts using puzzle game in class IV SDN Ponteh 1 Pamekasan. This research used the PTK (Classroom Action Research) method which was conducted on October 26, 2024. The results showed that the puzzle game was eﬀective in increasing students involvement with 100% of students successfully completing the puzzle correctly. The activity of arranging the puzzle according to the instructions given by the researcher makes students more enthusiastic in learning. This shows that an interesting learning strategy can increase student participation and the success of the learning process. It is expected that this puzzle game can be used sustainably to maintain student involvement, and be considered in learning with diﬀerent material.